2022
DOI: 10.1186/s12950-022-00301-2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic or therapeutic administration of Holarrhena floribunda hydro ethanol extract suppresses complete Freund’s adjuvant-induced arthritis in Sprague-Dawley rats

Abstract: Background A hydro ethanol extract of the stem bark of Holarrhena floribunda (HFE) has been shown to be effective in the management of acute inflammation. This study was to evaluate usefulness of the extract for the management of chronic inflammation in a murine model. Methods Arthritis was induced in Sprague-Dawley rats using Complete Freund’s Adjuvant. Anti-arthritic effect of the extract was evaluated in prophylactic and therapeutic treatment mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
(63 reference statements)
1
1
0
Order By: Relevance
“…Our study revealed a significant reduction in adenosine levels within the FCA model, which aligns with previous observations in the FCA model of female Wister rats (Arunsi et al, 2022). Furthermore, previous research showed that FCA-treated Sprague-Dawley rats exhibit a lower level of cAMP (an adenosine precursor) (Antwi et al, 2022). This finding corroborated previous research showing that adenosine receptors in MH7A cells have an anti-inflammatory effect (Konishi et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…Our study revealed a significant reduction in adenosine levels within the FCA model, which aligns with previous observations in the FCA model of female Wister rats (Arunsi et al, 2022). Furthermore, previous research showed that FCA-treated Sprague-Dawley rats exhibit a lower level of cAMP (an adenosine precursor) (Antwi et al, 2022). This finding corroborated previous research showing that adenosine receptors in MH7A cells have an anti-inflammatory effect (Konishi et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…Our study revealed a significant reduction in adenosine levels within the FCA model, which aligns with previous observations in the FCA model of female Wister rats ( Arunsi et al, 2022 ). Furthermore, previous research showed that FCA-treated Sprague-Dawley rats exhibit a lower level of cAMP (an adenosine precursor) ( Antwi et al, 2022 ). This finding corroborated previous research showing that adenosine receptors in MH7A cells have an anti-inflammatory effect ( Konishi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%